Komunikasi Lingkungan Dalam Komunikasi Islam - Fahmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This study needs to be studied to understand environmental communication in the concept of Islamic communication. The basic concept needs to be understood that Aceh is faced with various kinds of environmental problems that threaten the sustainability of eco-systems, biodiversity, and deterioration of environmental quality. This will also have an impact on increasing the intensity of disasters and decreasing the health quality of the community. Therefore, collective awareness is needed to save a balanced and sustainable environment. The aspect of environmental communication management is a strategic approach to building the collaboration of the parties in making people, industries, companies, governments and anyone aware of having a common awareness and strategy in the context of saving a quality, harmonious and sustainable environment. In the Islamic perspective, communication is an integral part of human life. One of the purposes of communication in Islam is to spread moral values derived from the Qur’an. In the Qur’an, it has been regulated about the procedures for how humans relate to humans and to the environment.